2016
DOI: 10.1016/j.ydbio.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest requires Impdh 2 for development of the enteric nervous system, great vessels, and craniofacial skeleton

Abstract: Mutations that impair the proliferation of enteric neural crest-derived cells (ENCDC) cause Hirschsprung disease, a potentially lethal birth defect where the enteric nervous system (ENS) is absent from distal bowel. Inosine 5′ monophosphate dehydrogenase (IMPDH) activity is essential for de novo GMP synthesis, and chemical inhibition of IMPDH induces Hirschsprung disease-like pathology in mouse models by reducing ENCDC proliferation. Two IMPDH isoforms are ubiquitously expressed in the embryo, but only IMPDH2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 69 publications
1
13
0
Order By: Relevance
“…For this study, we investigated the role of Tbx3, a transcription factor that is highly expressed in developing ENS relative to other cells of the bowel. We demonstrated that Wnt1-Cre efficiently depleted TBX3 from ENCDC, as expected since prior studies show Wnt1-Cre induces almost complete recombination in the ENS lineage (Lake et al, 2016). We found that Tbx3 is not required within ENCDCs for prenatal bowel colonization by ENS precursors, that Tbx3 fl/fl; Wnt1-Cre mice had a normal density of enteric neurons at P0, and that transit of FITC-dextran though the upper gastrointestinal tract occurred at a normal rate despite a reduced number of enteric glia.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For this study, we investigated the role of Tbx3, a transcription factor that is highly expressed in developing ENS relative to other cells of the bowel. We demonstrated that Wnt1-Cre efficiently depleted TBX3 from ENCDC, as expected since prior studies show Wnt1-Cre induces almost complete recombination in the ENS lineage (Lake et al, 2016). We found that Tbx3 is not required within ENCDCs for prenatal bowel colonization by ENS precursors, that Tbx3 fl/fl; Wnt1-Cre mice had a normal density of enteric neurons at P0, and that transit of FITC-dextran though the upper gastrointestinal tract occurred at a normal rate despite a reduced number of enteric glia.…”
Section: Discussionsupporting
confidence: 88%
“…For this study, Wnt1-Cre; Rosa26EYFP reporter mice were employed for fluorescence-activated cell sorting to separate EYFP expressing ENCDC from other cells of the bowel wall. This is a commonly used mouse line that expresses EYFP in essentially all ENCDC (>99.9%), but not in other cells of the bowel wall (Lake et al, 2016). As expected, we identified many differentially expressed genes encoding transcription factors, as well as other proteins (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Furthermore, Lake et al reported that inhibiting inosine 5′ monophosphate dehydrogenase 2 (Impdh2) produced defects in multiple neural crest derivatives, including intestinal aganglionosis, agenesis of the craniofacial skeleton, and cardiac outflow tract with malformations of major vessels. 19,22…”
Section: Teratogen-induced Models Of Hscrmentioning
confidence: 99%
“…MPA blocks the rate-limiting step of de novo guanine nucleotide synthesis by inhibiting inosine 5’ monophosphate dehydrogenase (IMPDH), a ubiquitous metabolic enzyme whose expression is relatively enriched in ENCCs. To further explore the role for this basic metabolic pathway, Lake et al recently deleted Impdh2 using a conditional allele crossed with the Wnt1-Cre transgene, and observed defects in multiple neural crest derivatives, including highly penetrant intestinal aganglionosis, agenesis of the craniofacial skeleton, and cardiac outflow tract with great vessel malformations (Lake et al, 2016). ENS defects in mutants lacking Impdh2 within the neural crest are clearly visible from E13.5 and demonstrate a critical role for de novo guanine nucleotide biosynthesis in ENS development.…”
Section: Beyond Genes: Roles For Regulatory Sequences Mirnas and Envmentioning
confidence: 99%